Direct deposition of extremely low interface-contact-resistant Ti2AlC MAX-phase coating on stainless-steel by mid-frequency magnetron sputtering method. Issue 8 (July 2020) - Abbas, Nadeem; Qin, Xiande; Ali, Shoukat; Zhu, Guangming; Lu, Jinglian; Alam, Fakhr e; Wattoo, Abdul Ghaffar; Zeng, Xierong; Gu, Kunming; Tang, Jiaoning
Abstract: MAX-phase materials, bulk as well as film, have manifested outstanding potential applications owing to their unusual properties. Usually, MAX-phase is achieved after higher ex-situ post-annealing (≥1000 ℃) treatment. Here, we report single-step transition to Ti2 AlC MAX-phase, deposited on stainless-steel(SS) by mid-frequency magnetron-sputtering system, at a lower substrate temperature of 750 ℃. The microstructure, phase and morphological characterization reveals that the compact, dense and crack-free film comprises of randomly oriented grains. Importantly, the surface of the film still remains crack-free after transition to the MAX-Phase. Moreover, a large improvement in conductivity for the film deposited at 750 ℃ (ICR = 3.27 mΩ.cm 2 under 140 N. cm −2 ) as compared to Ti-Al-C film deposited at 500 ℃ (ICR ≥ 400 mΩ.cm 2 ) elucidates the MAX-phase formation. The films with such low ICR values (<10 mΩ. cm 2 ; department-of-energy(DOE) standards) are the best potential candidates for future bipolar plates coating.